2022
DOI: 10.3390/s22020511
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Behavior of Masonry Shear Walls Retrofitted with Engineered Cementitious Composite and Pseudoelastic Shape Memory Alloy

Abstract: The behavior of masonry shear walls reinforced with pseudoelastic Ni–Ti shape memory alloy (SMA) strips and engineered cementitious composite (ECC) sheets is the main focus of this paper. The walls were subjected to quasi-static cyclic in-plane loads and evaluated by using Abaqus. Eight cases of strengthening of masonry walls were investigated. Three masonry walls were strengthened with different thicknesses of ECC sheets using epoxy as adhesion, three walls were reinforced with different thicknesses of Ni–Ti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The results showed that this method improved the bearing capacity and ductility of the wall and delayed strength degradation. In order to solve the problem of brittle cracking of ordinary concrete, Tabrizikahou et al [140] combined Ni-Ti SMA strips and ECC to form an SMA-ECC shear wall and used Abaqus software (https://www.3ds.com/products/simulia/abaqus) for evaluation, as shown in Figure 14d. The results revealed that the combination of the two methods improved the shear wall's energy dissipation capacity and led to a superior self-resetting ability and self-healing ability, thereby improving the seismic performance and durability of the shear wall structure.…”
Section: Sma-reinforced Shear Walls and Concrete Slabsmentioning
confidence: 99%
“…The results showed that this method improved the bearing capacity and ductility of the wall and delayed strength degradation. In order to solve the problem of brittle cracking of ordinary concrete, Tabrizikahou et al [140] combined Ni-Ti SMA strips and ECC to form an SMA-ECC shear wall and used Abaqus software (https://www.3ds.com/products/simulia/abaqus) for evaluation, as shown in Figure 14d. The results revealed that the combination of the two methods improved the shear wall's energy dissipation capacity and led to a superior self-resetting ability and self-healing ability, thereby improving the seismic performance and durability of the shear wall structure.…”
Section: Sma-reinforced Shear Walls and Concrete Slabsmentioning
confidence: 99%
“…Experimental and numerical studies proved stable rocking behavior without significant residual rotations. More recently, numerical investigations regarded the employment of pseudoelastic Ni-Ti SMA strips and engineered cementitious composite (ECC) sheets in masonry reinforcement demonstrating the enhancement of the energy absorption capacity and the stiffness of masonry walls [11].…”
Section: Sma Applications In Masonry Retrofitmentioning
confidence: 99%
“…The impact of applying different contact characteristics (tie, adhesive, surface-to-surface) is explored in another publication by the authors [ 24 ]; the contact properties between SMA stripes and masonry prism were established in the present study based on those results. An adhesive contact with tie interaction was employed to embed the SMA strips on the exterior surface of the masonry prisms.…”
Section: Description Of the Finite Element Modelsmentioning
confidence: 99%
“…Tabrizikahou et al [ 24 ] numerically analyzed the application of a novel hybrid retrofitting method using SMA stripes embedded in engineered cementitious composite (ECC) installed on masonry brick walls. A parametric analysis was carried out to investigate the effect of different retrofitting factors on the cyclic behavior of the masonry walls.…”
Section: Introductionmentioning
confidence: 99%